Challenges and Prospects of Enterprise Resource Planning (ERP) Systems in the Newly Chartered Public Universities in Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
Enterprise resource planning (ERP) systems have been the most popular business management systems in the 21st century, providing benefits of real-time capabilities, enhancing organizational competencies and seamless communication for business in both small and large organizations. Today, most universities have begun replacing their legacy systems with ERP initiatives to improve management and administration. Though they are credited with major prospects of re-engineering the work processes, these initiatives present some challenges to the management of these universities. This study focused on the challenges and prospects of ERP systems in the newly chartered public universities in Kenya. A review of previous studies on the challenges and prospects of putting in place this framework in public sector including universities was done. A descriptive survey research design was used to select the staff in all the 24 newly chartered universities in Kenya, while simple random sampling method was used in choosing 120 respondents who were heads of departments. A five point Likert scale questionnaire was used for data collection. A reliability estimate of 0.69 was realized for the instrument using Cronbach reliability coefficient. Data collected was analysed using descriptive statistics and presented in tables and charts. The study established that management support is vital for any organization to be able to successfully implement and use ERP systems effectively. In addition, inadequate preparation by the universities to manage change, failure to involve end-users during the implementation stage, failure by the system vendors to modify the system to conform to the requirements of these universities, failure by the institutions to re-engineer their business processes to match ERP requirements and lack of effective end-user training were also cited as the challenges facing the success of the ERP systems in the newly chartered universities. The findings further indicated successful implementation of the system will eliminate redundant tasks and lead to an overall reduction of operational cost. It will also lead to easier access to reliable data and information, improved customer relationship and the ability to produce better reports and information are some of the prospects that majority of the respondents believe the ERP system will provide. This study may be useful to public universities management by helping them gain better understanding on how to utilize information technologies. It also provides information that will assist them in making informed decisions on the best ERP implementation strategies to be employed. Lastly, the study will creates a forum for discussions on ways of solving ERP challenges currently being faced by the newly chartered public universities in Kenya.